Volume 11: New Developments in Simulation Methods and Software for Engineering Applications; Safety Engineering, Risk Analysis 2010
DOI: 10.1115/imece2010-40431
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of NOx Reduction in an Ammonia-SCR System With an Fe-Zeolite Catalyst and Calibration of Related Parameters

Abstract: NOx reduction in a single representative channel of an SCR converter is modeled accounting for convective mass transfer along the channel, diffusive mass transfer and chemical reactions within the catalytic layer, coupled via mass transfer boundary condition at the wall. The proposed 1D+1D code for the channel has different parameters involving rate expression constants for the surface chemistry and properties of the catalytic and washcoated layer. A comprehensive set of experimental data on the Fe-Zeolite was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…To simulate the behaviour of the SCR process, one representative channel was selected. The model, which was described thoroughly by Sharifian et al, 1 accounts for the convective mass transfer through the channel, the diffusive mass transfer and the chemical reactions within the catalytic layer coupled together via the mass transfer boundary condition at the wall…”
Section: Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…To simulate the behaviour of the SCR process, one representative channel was selected. The model, which was described thoroughly by Sharifian et al, 1 accounts for the convective mass transfer through the channel, the diffusive mass transfer and the chemical reactions within the catalytic layer coupled together via the mass transfer boundary condition at the wall…”
Section: Modelmentioning
confidence: 99%
“…Intra-porous diffusion limits ammonia adsorption on the catalytic surface within the washcoated layer and consequently influences NO x reduction, as was clearly demonstrated, for example, by Chatterjee et al 16 and Mladenov et al 16,18 Using a more simplified model neglecting intra-porous diffusion within the washcoat, such as a one-dimensional model, was seen to be insufficient also for the catalyst used in this study, as shown in by Sharifian. 19 The diffusion within the catalytic layer was described by…”
Section: Modelmentioning
confidence: 99%
See 3 more Smart Citations